Research competence of community nurses in Shanghai: A cross‐sectional study. (7th September 2022) - Hu, Yule; Liang, Tao; Li, Wanhui; Wan, Jia; Liu, Xin; Zhao, Hong; Wang, Li
Abstract: Aims: This study aimed to investigate the current situation of community nurses' research competence in Shanghai, to provide a basis for curricula design for nursing schools, construction of better research environments and nurturing research talents among community nurses. Background: Nurses are expected to not only consume research findings but also produce knowledge. In China, there is more attention on cultivation of community nurses' research competence. However, the current status of it remains unclear. Methods: This study employed convenience sampling to recruit a total of 2562 community nurses in Shanghai from June to August 2021. The study questionnaire included personal and job‐related characteristics, research competence and barriers to nursing research practice. Pearson's χ 2 tests (or Fisher exact probability method) and binary logistic regression analysis were used to analyse associated factors. Results: Our data showed that the overall research competence was 38.00 (28.00, 60.00) (best possible score, 120), which was at a low level. The binary logistic regression analysis results showed that nurses at the vice‐senior level and above, those without management roles or those who had research education/training experience had a higher level of research competence ( p < .05). Besides, a higher level of research competence was also seen in nurses who had attended academic conferences above the municipal level in the last 5 years, those with plans to upgrade educational levels or those who had positive attitude towards research ( p < .05). Our analysis demonstrated that limited English proficiency, data analysis and thesis writing, and lack of up‐to‐date research information and research mentors were the main barriers to effective community research practice. Conclusions: Our analysis showed that most of the community nurses had high demand for research training courses. Their research competence should be improved. In nursing educational and professional context, nursing administrators should pay more attention to provision of better learning, working and research environments. Implications for Nursing Management: Nursing administrators should establish a community nursing research culture, develop continuous training on research and prioritize recruitment and cultivation of scientific research talents.